The Role of HRM Factors in Improving Performance Analysis of Local Government Financial Reports - Susanto, Yohanes; Rambano, Dheo (Golden Ratio of Human Resource Management, 2022)
The central government authorized the local government to manage its finances independently in the regional autonomy system. The local government system must be transparent and accountable. The Report on Local Government Finances is one of the government tools to accountable it. However, based on the audit report in 2017, the Local Government Finances the Government of Musirawas, South Sumatera, Indonesia found inaccuracy. The research aims to examine the factors that influence the quality of the Local Government Finance of the Government of Musirawas, South Sumatera, Indonesia. The number of respondents is 110 persons from the government apparatus who represent their working unit of the Finance Management in the Government of Mursirawas, South Sumatera, Indonesia. The research utilizes a Structural Equation Modelling (SEM) method.   The research results showed that the Performance quality of the LAPD in the Government of Musirawas, South Sumatra, Indonesia, is simultaneously influenced by the competency of the Apparatus human resources, motivation, and the local accounting system; partially, it was influenced by the apparatus human resource competency.